High Temperature Solid-catalized Transesterification for Biodiesel Production - A. Brucato; A. Busciglio; F. Di Stefano; F. Grisafi; G. Micale; F. Scargiali (Chemical Engineering Transactions, 2010)
Abstract preview not available - see full-text PDF article.